ستخدام طريقة التخصيص في اختيار العطاء الأمثل دراسة تطبيقية في مشروع إنشاء القناطر الأنبوبية في محافظة اربيل - عمر, صادق حمد; سعيد, محمد رؤوف (Sulaimani Journal for Humanities, 2000)
Economical project are considered to be vivid cells of economical system, their essential task is to fulfill basic objects as minimization of costs & increasing benefit level. This research deals with suitable way for fulfilling the aim of fundamental projects. It has adopted appropriation style, the style adopted conuntries. This research attempts to solve a serious problem that many economical projects suffer from, the problem caused by low income & high requirements. The assumption of this research is that we could adopt that style for reducing cost levels. The research consisted of five parts: 1. The objects of the projects. 2. Minimization of cost level. 3. Minimization style. 4. Appropriation. 5. Practical aspect.